Hydrolysis products of agricultural waste can serve as microbial fertilizer enhancers to promote the growth of maize crops - Xu, Yu; Wang, Wei; Wang, He; Tian, Yinping; Yue, Zhengfu; Li, Cheng; Wang, Yuefeng; Zhang, Jing; Zhang, Ruifu (Frontiers in Plant Science, 2024)
Efficient utilization of agricultural wastes and reduction of chemical fertilizer inputs are crucial for sustainable development of agriculture. Plant growth promoting rhizobacteria (PGPR) are widely used as biofertilizers to partially replace chemical fertilizers in agricultural production. The functional performance of PGPR strains is closely related to their root colonization capacity. Some organic acids from root exudates can recruit PGPR to colonize the root. In this study, agricultural organic wastes such as mushroom bran and tobacco waste materials were used to produce organic acids through the hypoxic hydrolysis process. The hydrolysis conditions were optimized to maximize the production of a mixture of complex organic acids from the hypoxic hydrolysis of these materials, employing both single-factor and orthogonal experimental methods. The diluted hydrolysates were tested for their effects on the rhizosphere colonization of the PGPR strain Bacillus amyloliquefaciens SQR9 using fluorogenic quantitative PCR in greenhouse pot experiments. The results demonstrated that hypoxic hydrolysates from tobacco waste and mushroom bran significantly enhanced the colonization of SQR9 in the maize rhizosphere. Specifically, a 2000-fold dilution of tobacco waste hydrolysate yielded the most effective result, while a 5000fold dilution of mushroom bran hydrolysate provided the best outcome. All treatments combining these hydrolysates with SQR9 significantly increased maize stem dry weight, indicating that with appropriate treatment, such as anaerobic fermentation, these agricultural organic wastes can serve as synergistic agents of microbial fertilizers, contributing to agricultural sustainability.